Clinical and Pathological Complete Remission in a Patient With Metastatic Renal Cell Carcinoma (mRCC) Treated With Sunitinib: Is mRCC Curable With Targeted Therapy? - Amishi Y. Shah; Jose A. Karam; Zita D. Lim; Chaan S. Ng; Nizar M. Tannir (Urology Case Reports, 2015)
We report a patient with metastatic clear-cell renal cell carcinoma (mRCC) who presented with primary tumor in situ in the left kidney and metastases to bone, liver, lungs, and brain. After over 5 years of sunitinib therapy and subsequent cytoreductive left nephrectomy, the patient achieved radiographic complete response (CR) and had pathologic CR in the nephrectomy specimen. Durable clinical and pathological CRs are possible with targeted agents, even with primary tumor in situ and widely disseminated metastases. Ongoing research will define the optimal duration of systemic therapy in exceptional responders and identify the molecular determinants of response and resistance.